2017
DOI: 10.1021/acs.est.7b00178
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Sanitation Coverage More Strongly Associated with Child Growth and Household Drinking Water Quality than Access to a Private Toilet in Rural Mali

Abstract: Sanitation access can provide positive externalities; for example, safe disposal of feces by one household prevents disease transmission to households nearby. However, little empirical evidence exists to characterize the potential health benefits from sanitation externalities. This study investigated the effect of community sanitation coverage versus individual household sanitation access on child health and drinking water quality. Using a census of 121 villages in rural Mali, we analyzed the association of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 35 publications
5
71
1
Order By: Relevance
“…A recent trial in Cote d’Ivoire reported greater reduction in hookworm infection prevalence among communities that received a community-led total sanitation intervention (designed to reduce open defecation levels) integrated with community-wide MDA compared to community-wide MDA alone (32). A second explanation may be that sanitation interventions are more effective at interrupting environmental transmission of pathogens when they are implemented at the community level(33), whereas our intervention only improved sanitation access in compounds with enrolled pregnant women.…”
Section: Discussionmentioning
confidence: 96%
“…A recent trial in Cote d’Ivoire reported greater reduction in hookworm infection prevalence among communities that received a community-led total sanitation intervention (designed to reduce open defecation levels) integrated with community-wide MDA compared to community-wide MDA alone (32). A second explanation may be that sanitation interventions are more effective at interrupting environmental transmission of pathogens when they are implemented at the community level(33), whereas our intervention only improved sanitation access in compounds with enrolled pregnant women.…”
Section: Discussionmentioning
confidence: 96%
“…These two studies do not provide strong evidence for the effect of reaching high coverage with a latrine intervention on diarrhea. Observational research has found that community sanitation coverage is related to child height and stunting in Mali and Ecuador [9,10]. One observational study from national survey data in India found that community coverage was related to diarrhea [115], but another observational study found no effect of community coverage on diarrhea in Mali [9].…”
Section: Intervention Coveragementioning
confidence: 99%
“…Observational research has found that community sanitation coverage is related to child height and stunting in Mali and Ecuador [9,10]. One observational study from national survey data in India found that community coverage was related to diarrhea [115], but another observational study found no effect of community coverage on diarrhea in Mali [9]. Additional theoretical model analysis has suggested that all benefits from sanitation interventions come from the indirect effects due to community coverage [116].…”
Section: Intervention Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…Clasen et al (2014) proposed that there were not clear health differences because over a third of households in the intervention communities did not have a latrine. Households without latrines may still contaminate the surrounding environment and water sources that have adverse health impacts on households in the same community with latrines (Harris et al, 2017). Moreover, presence of a latrine does not necessarily indicate use as other household members may still open defecate particularly children.…”
Section: The Relationship Between Sanitation and Diseasementioning
confidence: 99%